Relevansi kajian hakikat manusia dengan habituasi sebagai metode pendidikan Islam - Milah, Saepul; Syihabuddin; Somad, Momod Abdul; Hidayat, Mupid (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The purpose of this study is to find the relevance between human nature and habituation as a method of Islamic education. The method used in this study is a descriptive method with a qualitative paradigm. The data collection technique used is a literature study, using four primary data sources, namely: 1) The book Tarbiyah al-Aulâd fî al-Islâm by Abdullah Nashih Ulwan, 2) The book Usus at-Tarbiyyah al-Islâmiyyah fî as-Sunnah an-Nabawiyyah by Abdul Hamid ash-Shaid az-Zintani, 3) The book Al-Fawâ'id by Ibn al-Qayyim al-Jauziyyah, and 4) the article